2018
DOI: 10.1098/rstb.2018.0012
|View full text |Cite
|
Sign up to set email alerts
|

Evolved tolerance to freshwater salinization in zooplankton: life-history trade-offs, cross-tolerance and reducing cascading effects

Abstract: One contribution of 23 to a theme issue 'Salt in freshwaters: causes, ecological consequences and future prospects'.Recent discoveries have documented evolutionary responses to freshwater salinization. We investigated if evolutionary responses to salinization exhibit life-history trade-offs or if they can mitigate ecological impacts such as cascading effects through mechanisms of tolerance and cross-tolerance. We conducted an outdoor mesocosm experiment using populations of Daphnia pulex-a ubiquitous algal gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…Bourdeau, Bach, & Peacor, 2016;Carpenter et al, 1985) and recent studies show that predator effects can interact with road salt. Although this effect triggered a trophic cascade leading to phytoplankton blooms, the authors found few effects in the absence of fish predation on zooplankton communities, perhaps due to rapid adaptation of zooplankton to the salt concentrations (Coldsnow, Mattes, Hintz, & Relyea, 2017;Hintz, Jones, & Relyea, 2019). Hintz et al (2017) also showed that concentrations of 1,000 mg Cl − /L and fish predation had a negative synergistic effect on the richness and abundance of experimental zooplankton communities.…”
Section: Lake Communitiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Bourdeau, Bach, & Peacor, 2016;Carpenter et al, 1985) and recent studies show that predator effects can interact with road salt. Although this effect triggered a trophic cascade leading to phytoplankton blooms, the authors found few effects in the absence of fish predation on zooplankton communities, perhaps due to rapid adaptation of zooplankton to the salt concentrations (Coldsnow, Mattes, Hintz, & Relyea, 2017;Hintz, Jones, & Relyea, 2019). Hintz et al (2017) also showed that concentrations of 1,000 mg Cl − /L and fish predation had a negative synergistic effect on the richness and abundance of experimental zooplankton communities.…”
Section: Lake Communitiesmentioning
confidence: 98%
“…Hintz et al (2017) also showed that concentrations of 1,000 mg Cl − /L and fish predation had a negative synergistic effect on the richness and abundance of experimental zooplankton communities. Although this effect triggered a trophic cascade leading to phytoplankton blooms, the authors found few effects in the absence of fish predation on zooplankton communities, perhaps due to rapid adaptation of zooplankton to the salt concentrations (Coldsnow, Mattes, Hintz, & Relyea, 2017;Hintz, Jones, & Relyea, 2019). Road salt concentrations ≥860 mg Cl − /L and non-consumptive predatory stress can also negatively affect zooplankton abundance in an additive way, and natural stress responses by zooplankton to predators (e.g.…”
Section: Lake Communitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of salinity change, dispersal could minimise changes in community structure by allowing salinity-intolerant organisms to be replaced by salinity-tolerant groups that possess similar traits. A few past studies support the second assumption, as there is evidence that zooplankton can evolve to tolerate higher salinity levels (Coldsnow et al, 2017;Hintz et al, 2018) and that there are differences in salinity tolerance both within and among species (EPA, 1988;Weider & Hebert, 1987). Under this scenario, overall trait diversity might be unaffected by salinisation and minimal changes in community structure might occur despite changes to the list of species or phenotypes present.…”
Section: Introductionmentioning
confidence: 96%
“…It is difficult to evaluate the first assumption without field studies in the region of interest, as published studies on zooplankton dispersal differ widely in their conclusions about dispersal rates (Audet et al, 2013;Cohen & Shurin, 2003;Havel & Shurin, 2004;Jenkins & Underwood, 1998;Jenkins, 1995;Márquez & Kolasa, 2013;Vanschoenwinkel et al, 2008b). A few past studies support the second assumption, as there is evidence that zooplankton can evolve to tolerate higher salinity levels (Coldsnow et al, 2017;Hintz et al, 2018) and that there are differences in salinity tolerance both within and among species (EPA, 1988;Weider & Hebert, 1987). Manipulative experiments also provide some support for the idea that dispersal can act to buffer against community change in the case of small increases in salinity (Symons & Arnott, 2013;Thompson & Shurin, 2012) or when zooplankton are exposed to other stressors such as nutrient enrichment (Forrest & Arnott, 2006), acidification (Steiner et al, 2011) and introduced predators (Howeth & Leibold 2010).…”
Section: Introductionmentioning
confidence: 99%